Pengaruh Model Problem Based Learning (PBL) terhadap Peningkatan Kemampuan Koneksi Matematis Siswa - Hafsah Adha Diana (Idealmathedu: Indonesian Digital Journal of Mathematics and Education, 2019)
This study aimsto analyze the effect of PBL and direct learning model towards improvement of mathematical connection ability, anlysed based on the initial mathematics ability of senior high school students at North Bekasi. This is a quasi experiment research. The treatment of PBL model was applied to the experiment class, while the controling class applied a direct learning model. The population of this study was the students of SMA Negeri 4 Kota Bekasi grade XI IPA academic year 2016/2017 whic was a normal population consisting of homogenous students. The instruments used consisted of mathematical connection ability test, initial mathematical ability test. Prior to the aplication, the instrument has passed the test of content validity, construct validity, and empirical validity. Data analysis was done using two-way Anava test and t-test. Based on the research results, it is found that: (1) improvement of student’s mathematical connection ability given PBL model treatment is higher than those direct instruction models was applied. (2) there is an interaction between the learning model and the initial mathematical ability to improve students' mathematical connection ability. (3) the improvement of mathematical connection ability of students with high mathematics initial ability to whom PBL model was applied is higher compared to students who got direct learning model treatment.